The R2R3 Transcription Factor CsMYB59 Regulates Polyphenol Oxidase Gene CsPPO1 in Tea Plants (Camellia sinensis) - Huang, Xiangxiang; Ou, Shuqiong; Li, Qin; Luo, Yong; Lin, Haiyan; Li, Juan; Zhu, Mingzhi; Wang, Kunbo (Frontiers in Plant Science, 2021)
Polyphenol oxidase (PPO) plays a role in stress response, secondary metabolism, and other physiological processes during plant growth and development, and is also a critical enzyme in black tea production. However, the regulatory mechanism of PPO genes and their activity in tea plants is still unclear. In this study, we measured PPO activity in two different tea cultivars, Taoyuandaye (TYDY) and Bixiangzao (BXZ), which are commonly used to produce black tea and green tea, respectively. The expression pattern of CsPPO1 was assessed and validated via transcriptomics and quantitative polymerase chain reaction in both tea varieties. In addition, we isolated and identified an R2R3-MYB transcription factor CsMYB59 that may regulate CsPPO1 expression. CsMYB59 was found to be a nuclear protein, and its expression in tea leaves was positively correlated with CsPPO1 expression and PPO activity. Transcriptional activity analysis showed that CsMYB59 was a transcriptional activator, and the dual-luciferase assay indicated that CsMYB59 could activate the expression of CsPPO1 in tobacco leaves. In summary, our study demonstrates that CsMYB59 represents a transcriptional activator in tea plants and may mediate the regulation of PPO activity by activating CsPPO1 expression. These findings provide novel insights into the regulatory mechanism of PPO gene in Camellia sinensis, which might help to breed tea cultivars with high PPO activity.